Effects of Supervisory Support and Core Self- Evaluation in Predicting Work Disengagement among Nurses in Public Hospitals in Pakistan - Malik, Haider Ali; Haider, Ghazala; Hashim, Muhammad; Bhatti, Anam; Javaid, Anam (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to know the association between supervisory supports, core self-evaluation and disengagement from job. Public hospitals in major cities Pakistan (Islamabad and Rawalpindi) were the study population. The data were obtained through distribution of survey questionnaire from 278 nurses. Data collection was carried out using simple random technique. Hypotheses were developed on the basis of past literature and all hypotheses were accepted. Structural equation modeling technique was used for data analysis. The results showed that there was positive relationship between all variables. The study contributed in the literature of work disengagement, supervisor and self assessment. Implications and recommendations are provided for better work environment and avoidance of work disengagement among nursing staff.